Impact of Climate Change on Neurodevelopmental Disorders in Pediatrics - Padmanabhan, Srihari; Tharan, Ojaswin (Journal for Research in Applied Sciences and Biotechnology, 2024)
The present work aims at analyzing the effects of the climate change on neurodevelopmental disorders in children. The document dwells on the importance of neuro-toxic stressors in pollution and climatic changes affect neurological risks in children. Specifically, this research will examine the following questions: the causal mechanisms by which climate change impacts neurodevelopment; the related health consequences on children; and protective strategies for these populations. Through these linkages, the paper underscores the need for policy change and community mobilisation to protect children as they are affected by climate change.